Chapitre I. Sources primaires et récriture postmoderne - Lanone, Catherine (Presses Sorbonne Nouvelle, 2018)
A challenging read, Vollmann’s novel destabilizes the reader to offer a complex historical perspective which questions both today’s situation and the historical impact of nineteenth-century journeys of exploration. To begin with, Vollmann’s Rifles presents the North as a troubled ecosystem, highlighting cultural degradation and common addictions, as well as the impact of the “relocation policy” » of the fifties, and the Inuits’ current inability to make their voice heard and obtain compensation. A playful pastiche of Moby-Dick, the novel’s eponymous central chapter points to the dissemination of rifles as the main cause for decay.However, The Rifles is a novel of ecocriticism with a twist. The text plays with multiple sources, quotingand distorting, shifting compulsively back and forth in time, to demystify the heroic legend of Franklin’s expeditions. Vollmann maps the trips with accuracy, drawing inspiration from Victorian engravings and from Franklin’s early accounts, such as Narrative of a Journey to the Shores of the Polar Sea in the Years 1819-1822, but also tapping into recent discoveries and Beattie’s emphasis on lead poisoning, imagining the consequences of lead slowly seeping into minds and bodies. Thus Vollmann creates a pastiche of nineteenth-century narratives of exploration, complete with mock illustrations, maps and lists of names. But he also adds sarcastic counterpoints, from sudden blatant anachronistic shifts to incongruous juxtapositions and subtle shifts which cast an ironic light on the quotations from historical journals. Barthes’ concept of “myth” and Bourdieu’s analysis of the semiotic system of domination highlight Vollmann’s deconstruction of British icons. Thus Vollmann’s ironic historiographic metafiction plays on metamorphosis, rather than the slavish imitation of sources. Just as in the opening chapter the source of water cannot be located on the island, since the permafrost thaws temporarily on the surface to create multiple streams, Vollmann refuses to mimic sources but combines ...